Considerations about the strengths and áreas of opportunity in academics of the UAZ and UAQ: word performance, gender biases and life imprint (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2024)
One of the defining elements in the rise of women in the educational field has been the achievement of higher and postgraduate training, from which they have been able to conquer a workplace with better conditions and salaries, as well as climb positions. in decision-making and obtain quality indicators. In the case of Mexico, particularly belonging to the Program for the Professional Development of Teachers (PRODEP), the National System of Researchers (SNI), positioning in Consolidated Academic Bodies (CAC), access to the Program of Incentives for the Performance of Teaching Staff (ESDEPED), in addition to belonging to other instances or recognition networks, have been key to this improvement. In this situation, although the country's academics, especially in public universities, have gained ground, it is also indisputable that the balance that this has generated for them refers to gender biases in their work; hand in hand with some scenarios of gender-based violence and the imprint that the academic load has on their health, lives and family.This research proposes an analysis in two institutions: the Autonomous University of Zacatecas and the Autonomous University of Querétaro, taking as an object of study a sample of academics in both institutions, in order to reveal the scope of the areas of opportunity and strengths that define their work practice and life.